The Role Of The Supervisory Council Of The Regional Notary (MPD) In The Notary Code Enforcement Under Act No. 2 Of 2014 In Subang - Aep Saepudin; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this research is to know and understand the role of the Notary Supervisory Council of Regions (MPD) Based on Act No. 2 of 2014, and to know and understand the code of ethics enforcement practices notary office in Subang.Based on the results of data analysis is concluded, that obtained a description of some of the measures that will be implemented by the Council of Regional Supervising Notary Subang district, in addition to the authority in accordance with the rules of the existing Assembly Regional Supervising Notary Subang district also did sosilisasisosialisasi to the parties associated with the profession of Notary among other elements of society, academic elements, the Indonesian National Police. Regarding the agencies that supervise the Notary prior to the enactment UUJN conducted by the District Court results are not optimal this is due to a lack of understanding Supervisory Judge of the profession Notary, while supervision and examination of the Notary conducted by the Council of Trustees, in which there are elements of Notaries, thus at least Notary supervised and examined by the Supervisory Council members are definitely better understand the world Notary. Keywords: Notary Supervisory Council of Regions; Code; Notary.